Takhrij and Syarah Hadith of Agrotechnology The Virtue of Farming - Dimas Fitrah Andrea Apriandi; Jajang Supritana; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about the virtues of farming. This research method is qualitative through the takhrij and sharah hadith approaches with agrotechnological analysis. The results and discussion of this research are the virtues of farming according to scientific research. The conclusion of the research is takhrij and syarah hadith of the Prophet. about the virtue of farming with agrotechnology analysis to open new jobs in developing the Indonesian economy.